Em busca de um padrão de atendimento: o caso da secretaria da escola de pós-graduação em economia (EPGE) da Fundação Getulio Vargas (FGV) - Vidal Pérez, André (2003)
This work has as its objective to create a service¿s pattern to EPGE Secretary, so we can solve the endless stress of the quaternary sector organization, where teachers and secretary professionals just can¿t get along. This systemic model intends to create a definite solution to that problem, allowing teachers to dedicate their time only to research and orientation to students. That way, we can keep the high quality of the secretary¿s service, as we are the symbol of EPGE through the eyes of the public. Having done the theoretical conceptualization of Organizations, Systems and Methods and also Geertz Theory of Ethnography, we build a pattern system, adapted to FGV¿s secretaries cultural situation. A group of 21 professionals from FGV¿s secretaries was selected and through a qualitative research, it was sustained the six years field work of the thesis author. The group¿s contribution to this work was fundamental to build the model and can also create a new way of thinking the work from secretaries of FGV.